Dispositifs of Security (Foucault on Governing) - Romčević, Branko Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
In this paper, we start from theses on governing, developed in Foucault’s lectures from the course Security, Territory, Population (1978). Our goal is to use them, applying the method of close reading, to get to what he called the mechanisms and instruments of every governing, that is, to the dispositifs of security. In order to achieve this, we first consider the distinction that Foucault drew between the art of conduct and the art of government (governmentality), and then the distinction between regulation and governing. In this framework, we review the writings in which Foucault introduced the issues of biopower, discipline and biopolitics, and we find that in the 1978 lectures, he made a far-reaching change by linking biopolitics, previously defined as a regulatory technique, to governing. In the central part of the paper, we analyze his thematization of the economic rationale of governing and the determination of liberalism as a general paradigm of governmentality in the modern era, which results in a society that, as he says, is controlled by security dispositifs. The security program, unlike the disciplinary one, does not aim to abolish or suppress anything, but rather to determine the optimal average and bandwidth of the acceptable for each phenomenon. Then, discussing the similarities and differences between disciplinary dispositifs and sexuality dispositifs, established through Foucault’s books Discipline and Punish and Will to Knowledge (the first volume of the History of Sexuality), we ask the question about dispositifs in general. Then we apply the obtained findings to the constitution of the security dispositif as a way to embody that equilibrium (between optimal average and bandwidth of the acceptable) in the social reality. In the final part, we consider two cases (Frédéric Gros on the fourth age of security and Didier Bigo on the ban-opticon) of the application of Foucault’s theses to the period from the beginning of this century, emphasizing that the Foucauldian perspective, when all its constituents are taken into account, is neither pessimistic nor dystopian.